The Relationship Between Work Posture and Musculoskeletal Disorders (MSDs) Among Photocopying Workers Around Muhammadiyah University Surakarta - Sela Nurul Hikmah; Rezania Asyfiradayati (International Journal of Science and Environment (IJSE), 2026)
This study intends to evaluate the association between work posture and musculoskeletaldisorders (MSDs) among copier workers around Muhammadiyah University Surakarta. Thestudy used a quantitative approach with a cross-sectional design and was conducted inFebruary 2025 at photocopying businesses located in several areas around the campus,namely Duwet Raya Street, Mendungan Street, Garuda Mas Street, Gatak 1 Street, Gatak 2Street, and Menco Raya Street. Using total sampling technique, all 78 photocopying workersaround Muhammadiyah University Surakarta were included, and 56 people were willing toparticipate in the study. Work posture was examined using the Rapid Entire Body Assessment(REBA) method to establish the level of ergonomic risk, whereas MSDs complaints weremeasured using the Nordic Body Map (NBM) questionnaire. Data analysis was performedunivariately and bivariately using the Spearman Rank Correlation test with a significancethreshold of 0.05. The results showed that most workers were in the low to moderate and highergonomic risk categories, with the most prevalent MSDs complaints in the neck, back, waist,right wrist, and calves. The Spearman Rank test showed a significant, fairly strong, andunidirectional relationship between work posture and MSDs complaints (p-value = 0.000; r =0.531), indicating that an increase in work posture risk was followed by an increase inmusculoskeletal complaints among photocopying .